Postoperative radiotherapy of patients with cervical cancer – analysis of indications and evaluation of treatment results in the case of incomplete information about prognostic factors - Bajon, Tomasz; Roszak, Andrzej; Milecki, Piotr; Kaźmierska, Joanna; Wareńczak, Żaneta (Contemporary Oncology/Współczesna Onkologia, 2009)
Aim of study: To evaluate treatment results of radical and simple hysterectomy of patients with cervical cancer who received adjuvant radiotherapy as well as to evaluate the influence of prognostic factors on treatment results. Material and methods: The analysis included 86 patients with squamous cell carcinoma after surgery and adjuvant radiotherapy from 2000 to 2003. Thirty-one patients had radical hysterectomy with lymphadenectomy of the pelvis, of whom 24 patients (77.4%) were in stage IB, four (12.9%) in stage IIA and three (9.7%) in stage IIB. A simple hysterectomy was performed in 55 patients (63.9%), of whom 51 patients (92.7%) were in stage IB, four patients (7.3%) in stage IIA. Results: Five-year patient survival rates treated with radical and simple hysterectomy in stage I were comparable (79.1% and 80.4%). The ratio in stage II was 50.0% and 75.0% respectively. A significant difference in survival of patients (p < 0.05) with features N(–) (88.7%) was noticed, which is in contrast to patients with metastases in lymph nodes (50.3%). In the case of simultaneous absence of metastasis in lymph nodes and absence of parametria involvement or absence of invasion into the lymphovascular space, survival was 90.2% and 93.4% respectively, while in the case of absence of all these factors it was 100%. Conclusions: The high proportion of patients after simple hysterectomy (63.9%) instead of radical hysterectomy with pelvic lymphadenectomy means that surgeons failed to follow standard surgical procedures. The 5-year obser-vation results indicate that patients after radical hysterectomy with lymphadenectomy did not have better treatment results when compared with patients after simple hysterectomy.